Preparation of silk fibroin carriers for controlled release. Issue 3 (6th December 2015) - Liu, Qiang; Liu, Haifeng; Fan, Yubo
ABSTRACT: Silk fibroin provides a new option for controlled release systems as a result of its excellent biodegradability, biocompatibility, and mechanical properties. As the core material, silk fibroin can be designed and widely used in drug/gene delivery, regenerative medicine, and other biomedical fields. This review focuses on the preparation methods, loading molecules, and applications of silk fibroin‐based controlled release systems including microspheres, microcapsules, films, microparticles, microneedles, liposomes, and hydrogels. These systems provide numerous advantages such as high encapsulation efficiency, avoiding loss of bioactivity and maintaining desirable range without peaks and valleys in comparison to the traditional administration approaches. Microsc. Res. Tech. 80:312–320, 2017. © 2015 Wiley Periodicals, Inc.